Interactions of wolves, mountain caribou and an increased moose-hunting quota --- Primary-prey management as an approach to caribou recovery. - Steenweg, Robin W. (Author); Gillingham, Michael (Thesis advisor); University of Northern British Columbia (Degree granting institution) (University of Northern British Columbia, 2012)
Mountain caribou (Rangifer tarandus caribou) are endangered across their range. The leading cause of their decline is increased apparent competition with other ungulates, mainly moose (Alces alces), because of increase in densities of predators such as wolves (Canis lupus). I tested some assumptions of, and evidence for, moose management as an approach to caribou recovery through the indirect reduction in wolf numbers. Increased hunting quotas drastically reduced moose densities in the Parsnip River Study Area of northern British Columbia, and I monitored 31 collared wolves during this decline. Despite wolf selection for vegetation types associated with moose and avoidance of areas selected by caribou, wolves occasionally forayed during snow-free months to elevations where caribou were more common. Wolf diets were comprised of >80% moose, with little caribou and other prey items. Annual dispersal rates of wolves increased compared to rates before moose reduction, and compared to a control study area. In systems where moose comprise the majority of wolf diets and caribou are at low densities, reductions in moose numbers may help to facilitate caribou recovery. --P. ii. The original print copy of this thesis may be available here: http://wizard.unbc.ca/record=b1754822